A Study into the Pyramid Discussion Approach with Pre-Service English Teachers in Japan - Takaaki Hiratsuka (Indonesian TESOL Journal, 2021)
The main concern of this article is the nature and the role of an EFL classroom speaking activity, known as pyramid discussion, whereby learners progressively form larger groups as they carry out a series of discussions on certain topics. This research interest stemmed from my personal experiences as an English language teacher in the context of Japan in which the majority of the teachers still regard the act of teaching English as the presentation of compartmentalized knowledge, as opposed to the promotion of communicative abilities. In this article, I introduce an action research study into the employment of the pyramid discussion approach in an English Teaching Methods course at a Japanese university and illuminate the effectiveness of the approach on the students, who are pre-service English teachers, in the course. Data will detail how the approach could notably assist the participants in seizing communication opportunities in English and in holding positive attitudes toward their teacher, classmates, and themselves as learners and future teachers of English. Implications are provided as a conclusion